EFEITOS DO NITROPRUSSIATO DE SÓDIO (SNP) NA GERMINAÇÃO E CRESCIMENTO INICIAL DA ALFACE SOB ESTRESSE OSMÓTICO: DA PESQUISA À DIVULGAÇÃO CIENTÍFICA - Santos, Camila Reis dos (2020)
Abiotic stress leads to a series of physiological, biochemical and molecular changes that negatively affect plant growth and productivity. Drought and salinization, usually manifested as osmotic stress, are threats to agriculture in many cultures, especia